PENGARUH REBUSAN DAUN BINAHONG (Anredera cordifolia) TERHADAP KUALITAS SPERMATOZOA MENCIT (Mus musculus L.) DIABETES - Meliyana, Yeni; Sudiastuti, Sudiastuti; Nugroho, Rudy Agung (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This research aimed to evaluate the effect of decoction of the leaves binahong in improving of sperm quality of diabetic mice induced by alloxan. The quality of mice sperm including number of spermatozoa, motility and morphology of spermatozoa were determined after 30 days. Completed randomized design was use in this research, 30 mice were devided randomly into 5 groups (negative control, positive control, first treatment dose of 29 mg, 57 mg doses of treatment II and 114 mg doses of treatment III). The results of the quality of spermatozoa were presented as mean ± standar error (SE). Analysis of Variances (ANOVA) was used to determined statistical different among the group, followed by Duncan Multiple Range Test (DMRT) with significant level 95%. The results found that there was an increase in blood sugar levels followed by a decline in the number of spermatozoa, motility of spermatozoa (P>0,05) and the increase in abnormal morphology of spermatozoa (P<0,05) in all groups except the negative control after induced. After being given a dose of binahong decoction variation of the results showed that the number and motility of spermatozoa was highest in the group PIII that were given doses of 114 mg a mean number of spermatozoa (21016,00 ± 130,171) and motility of spermatozoa (34,33 ± 0,88). Meanwhile, the lowest morphological abnormal spermatozoa are group PIII with a mean of (79,33 ± 0,88). The conclusion of this study is a decoction of the leaves binahong is able to improve the quality of spermatozoa diabetic mice along with a decoction of the leaves binahong doses in increments.